Pengaruh Jenis Kemasan dan Penyimpanan Suhu Rendah Terhadap Perubahan Kualitas Cabai Merah Keriting Segar - Asmeri Lamona; Y. Aris Purwanto; Sutrisno . (Jurnal Keteknikan Pertanian, 2015)
During postharvest handling of red curly chili, transportation and temporary storage are critical step due to high losses. The objcctives of this study were to analyze the effect of packaging material and low temperature storage on the quality changes of fresh red curly chili and to determine the optimum combination of packaging material and temperature storage. After being harvested, samples of red curly chili were sorted and packed in differents packaging material of 3 kg and transported to the laboratory within 5 hours at ambient temperature condition. During storage period, the visual appearance, change in respiration rate, weight loss, firmness and color were measured. Waring, plastic sack and polipropilene plastic were selected as packaging materials, temperature of 10, 15OC and ambient temperature were set as storage temperature. The results show that packaging material and temperature storage influenced the respiration rate, weight loss and firmness of red curly chili. Lightness (L*) correlated only with packaging material. The interaction between packaging material and temperature storage has only correlation with weight loss. The highest losses of 21.06±0.4 was resulted for the combination of waring packaging at room temperature. The lowest losses of 0.12%±0.1 was found for the combination of polipropoline plastic packaging at 10OC. The longest storage period up to 29 days was found for those red curly chili stored at combination of polipropilene plastic packaging at 10OC.